Goose flocks and food finding: field experiments with Barnacle Geese in winter - Drent, R; Swierstra, P (Wildfowl, 1977)
Choice experiments involving two groups of model geese set out during the night on fields frequented by Barnacle Geese Branta leucopsis in the winter showed that, (1) the model flocks acted as a nucleus around which the geese landed as they arrived from the roost each morning, (2) a model flock composed of a majority of individuals in the grazing posture induced more landings, involving larger numbers and a longer duration of stay, than a model flock composed predominantly of individuals in the head-up ’alert’ posture. On the basis of observations of geese lured to already depleted pastures by the use of models, we speculate that the ’alert’ functions in food-finding in addition to predator detection, in agreement with the discussion of Dimond & Lazarus (1974).